An Analysis of The Opportunities and Challenges of Exporting Indonesian Acacia Wood Furniture to Japan Based on The Heckscher–Ohlin Theory - Nadya Sopie Ramadani (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
International trade remains an important mechanism for enhancing economic growth and expanding industrial competitiveness in resource rich economies. This study analyzes the opportunities and challenges associated with exporting Indonesian acacia wood furniture to Japan through the theoretical lens of the Heckscher Ohlin framework. The research adopts a non empirical qualitative design based on conceptual analysis and qualitative content interpretation. Secondary data were obtained from official trade statistics, government publications, and scholarly literature concerning comparative advantage, furniture exports, forest based industries, and international trade competitiveness. The findings indicate that Indonesia possesses favorable export prospects because its abundance of forest resources and labor availability support the production of acacia wood furniture with competitive cost structures. At the same time, export performance is constrained by intense international competition, stringent quality requirements, timber legality obligations, sustainability expectations, technological limitations, and logistics related challenges. The analysis further demonstrates that factor abundance alone is insufficient for sustaining long term competitiveness in the Japanese market. Future export performance increasingly depends on value added manufacturing, innovation, industrial upgrading, integration into global value chains, and stronger competitive capabilities. The study confirms the continued relevance of the Heckscher Ohlin theory while highlighting the necessity of complementing comparative advantage with strategic industrial transformation.